Depression and Anxiety Scores Are Associated with Amygdala Volume in Cushing's Syndrome: Preliminary Study. (18th May 2017) - Santos, Alicia; Granell, Esther; Gómez-Ansón, Beatriz; Crespo, Iris; Pires, Patricia; Vives-Gilabert, Yolanda; Valassi, Elena; Webb, Susan M.; Resmini, Eugenia
Abstract : Introduction . Cushing's syndrome (CS) has repeatedly been associated with hippocampal volume reductions, while little information is available on the amygdala, another structure rich in glucocorticoid receptors. The aim of the study was to analyze amygdala volume in patients with CS and its relationship with anxiety, depression, and hormone levels. Material and Methods . 39 CS patients (16 active and 23 patients in remission) and 39 healthy controls matched for age, sex, and education level completed anxiety (STAI) and depression tests (BDI-II) and underwent a 3 Tesla brain MRI and endocrine testing. Amygdala volumes were analysed with FreeSurfer software. Results . Active CS patients had smaller right (but not left) amygdala volumes when compared to controls (P = 0.045 ). Left amygdala volumes negatively correlated with depression scores (r = - 0.692, P = 0.003 ) and current anxiety state scores (r = - 0.617, P = 0.011 ) in active CS patients and with anxiety trait scores (r = - 0.440, P = 0.036 ) in patients in remission. No correlations were found between current ACTH, urinary free cortisol or blood cortisol levels, and amygdala volumes in either patient group. Conclusion . Patients with active CS have a smaller right amygdala volume in comparison to controls, while left amygdala volumes are associated with mood state in both patient groups.